2021
DOI: 10.21037/jgo-20-252
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of systemic immune-inflammatory index in survival outcome in gastric cancer: a meta-analysis

Fu S1,
et al.

Abstract: Background: In recent years, many studies have reported that the systemic immune-inflammatory index (SII) can be used to predict the prognosis of cancer patients; however, this finding remains controversial in gastric cancer (GC). Therefore, the purpose of this study was to systematically and comprehensively probe the prognostic role of SII in GC. Methods: Relevant publications were extracted from PubMed, EMBASE, Cochrane Library databases, and WANFANG DATA (Chinese database). The included studies had patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…Recently, it has been reported that the SII sore is of prognostic value in many malignant tumor types including hepatocellular carcinoma [ 37 ], gastric cancer [ 38 ], colorectal cancer [ 39 ], and urological and gynecological tumors [ 13 , 40 ]. Given that RCC is an inflammatory disease, the investigation of the SII score seems to be of particular interest in patients treated with immune checkpoint inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that the SII sore is of prognostic value in many malignant tumor types including hepatocellular carcinoma [ 37 ], gastric cancer [ 38 ], colorectal cancer [ 39 ], and urological and gynecological tumors [ 13 , 40 ]. Given that RCC is an inflammatory disease, the investigation of the SII score seems to be of particular interest in patients treated with immune checkpoint inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis that included 2,796 patients reported that a high SII was associated with poor prognosis in patients with hepatocellular carcinoma (44). Fu et al observed that a high SII was significantly associated with poor OS and DFS in patients with gastric cancer (45). Huang et al also reported that a high SII was associated with poor OS, PFS, and CSS in patients with urologic cancers (48).…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analyses have investigated the prognostic role of SII in many cancer types, including hepatocellular ( 44 ), gastric ( 45 ), breast ( 46 ), and colorectal cancer ( 47 ). A meta-analysis that included 2,796 patients reported that a high SII was associated with poor prognosis in patients with hepatocellular carcinoma ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al showed that an elevated preoperative SII was significantly associated with worse survival outcomes and adverse pathological features in patients with bladder cancer based on a meta-analysis of 7087 patients [ 49 ]. Fu et al reported that a higher SII value was significantly associated with worse OS and DFS in gastric cancer in a meta-analysis of 11 studies [ 50 ]. Another meta-analysis of 3180 patients revealed that a high SII was independently associated with poor survival outcomes in patients with renal cell carcinoma [ 51 ].…”
Section: Discussionmentioning
confidence: 99%